Policy change and policy learning in post-socialist wildlife policy in Slovenia - Šinko, Milan (Teorija in praksa, 2015)
The article is a case study of the formation of wildlife policy, taking hunting rights in Slovenia as a specific example. The main analytical goal is to identify the presence of policy learning in the formation of wildlife policy in the period 1990-2004. This was a period when, owing to the process of social and political transition, the dynamic of policy formation was particularly strong. The research model is based on the theory of policy learning and policy diffusion and incorporates a review of the existing body of research on policy learning in other transition countries and in Slovenia. To identify the presence of policy learning, we used indicators of instrumental, social and political learning. Our main hypothesis, namely, that policy learning was not the trigger of policy change, was tested by applying the following mechanisms of policy diffusion: emulation, coercion and economic competition. We demonstrated the presence of political learning which led to changes in hunting rights, corresponding to the concept of institutional adjustment or patching. Instrumental and social learning were not detected, nor were mechanisms of policy diffusion.
Keywords: Javna politika; learning; lovske pravice; lovstvo; politika divjadi; Public policy; Slovenia; Slovenija; Transition; Tranzicija; učenje